2004
DOI: 10.1192/pb.28.9.324
|View full text |Cite
|
Sign up to set email alerts
|

Audit of disposal of clinically confidential information

Abstract: Aims and MethodWe conducted a 3-cycle audit of disposal of clinically sensitive information in a mental health unit, in order to identify and reduce potential breaches in patients' confidentiality. Material from waste bins in administrative areas of a mental health unit was examined every evening during each period of the audit.ResultsThe first search, conducted over a 3-week period, yielded 11 documents containing highly-sensitive information about patients. After feedback to staff and improvement of shreddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…However, our findings are in keeping with previous audits in English hospitals, both published10 and unpublished. Insecure confidential document handling is not simply a Welsh trainee problem.…”
Section: Discussionsupporting
confidence: 93%
“…However, our findings are in keeping with previous audits in English hospitals, both published10 and unpublished. Insecure confidential document handling is not simply a Welsh trainee problem.…”
Section: Discussionsupporting
confidence: 93%
“…After removing duplicates, 2313 studies were screened by title and abstract, yielding 699 articles for full-text review. From that set, ultimately 156 studies were eligible for inclusion in the qualitative synthesis (Supplemental Table S1) (Abd El-Salam, 2010; Abu Qdais et al, 2007; Alam et al, 2008; Al-Dhawailie, 2011; Alhumoud and Alhumoud, 2007; Ali, 2019; Ali and Geng, 2018; Ali et al, 2016a, 2016b; Al-Khatib et al, 2019; Almeida et al, 2016; Almuneef and Memish, 2003; Altin et al, 2003; Alves et al, 2014; Al-Zahrani et al, 2000; Andrade et al, 2014; Asante et al, 2014; Askarian et al, 2010; Awad et al, 2004; Azage and Kumie, 2010; Babu et al, 2019; Barbario et al, 2021; Bassey et al, 2006; Bazrafshan and Mostafapoor, 2011; Bdour et al, 2007; Caniato et al, 2016; Carr et al, 2019; Chiang et al, 2006; Chitnis et al, 2005; Chua et al, 2021; Conrardy et al, 2010; Debere et al, 2013; Debita et al, 2017; Dehghani et al, 2008, 2019; Denny et al, 2019; de Sa et al, 2016; De Sousa et al, 2014; Dewi et al, 2019; Dias et al, 2017; Diehl et al,1992; Dietrich et al, 2004; Doiphode et al, 2016; Dumitrescu et al, 1998; Farmer et al, 1997; Farzadkiaet al, 2009; Fasola et al, 2008; Ferdowsi et al, 2012; …”
Section: Resultsmentioning
confidence: 99%
“…Safe management of medical waste can be extremely expensive, but in the United States, up to 85% of waste from hospitals does not need to be treated as infectious according to regulatory definitions (WHO, 2018). Physical waste audits in which components are measured can unveil issues in waste segregation, Almuneef and Memish, 2003;Diehl et al, 1992;Fasola et al, 2008;Garcia, 1999;Gunther, 2013, 2016;Mosquera et al, 2014;Nandwani, 2010;Reed et al, 2013 Educational programmes 11 (34%) Almuneef and Memish, 2003;Denny et al, 2019;Dietrich et al, 2004;Fraifeld et al, 2021;Hames, 2013;Nandwani, 2010;Reed et al, 2013;Soroceanu et al, 2011;Tisdall et al, 2019;Tudor, 2008;Zafar and Butler, 2000 Operational procedure changes 8 (25%) Debita et al, 2017;De Sousa et al, 2014;Diehl et al, 1992;Fasola et al, 2008;Grimmond and Reiner, 2012;Kron et al, 2021;Makofsky and Cone, 1993;Reed et al, 2013 Waste sorting changes 8 (25%) Diehl et al, 1992;Francis et al,1997;Moreira and Gunther, 2013;Lawlor, 2014;Mosquera et al, 2014;Debita et al, 2017;McGain et al, 2015;Fraifeld et al, 2021 Lean/Six Sigma/total quality management 4 (13%) Askarian et al, 2010;Furukawa et al, 2016a…”
Section: Discussionmentioning
confidence: 99%
“…Although patient lists have been shown to be an effective way to ensure efficient continuing care, 11 there is little published data regarding appropriate storage and disposal of patient lists. A recent study has reported the inappropriate disposal of a number of patient‐sensitive documents, including patient handover information, in general waste 12 . Much work has been carried out recently to identify possible pitfalls in the introduction of electronic storage of patient records, although our study is one of the few that addresses the storage and disposal of in‐patient lists and the potential benefits of DPT.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported the inappropriate disposal of a number of patient-sensitive documents, including patient handover information, in general waste. 12 Much work has been carried out recently to identify possible pitfalls in the introduction of electronic storage of patient records, although our study is one of the few that addresses the storage and disposal of in-patient lists and the potential benefits of DPT. There are several limitations to our study.…”
Section: Discussionmentioning
confidence: 99%